1989
DOI: 10.1007/bf02575427
|View full text |Cite
|
Sign up to set email alerts
|

Catheter occlusion of a mycotic renal artery aneurysm with cure of associated renovascular hypertension

Abstract: We describe successful transcatheter occlusion of a mycotic renal artery aneurysm. The patient's hypertension resolved following occlusion of the aneurysm and infarction of the renal parenchyma in the distribution of the aneurysmal vessel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Other causes include inflammation or infection (29). Traumatic pedicular aneurysms can be due to a direct wound or to dissection of the media due to deceleration in a car accident.…”
Section: Indicationsmentioning
confidence: 99%
“…Other causes include inflammation or infection (29). Traumatic pedicular aneurysms can be due to a direct wound or to dissection of the media due to deceleration in a car accident.…”
Section: Indicationsmentioning
confidence: 99%
“…Although the benefit of treating an aneurysm associated the aneurysmal sac. The use of NDCs to treat true aneurysms may have with hypertension is controversial, several authors have described significant improvements in hypertension after some disadvantages and risks, including uncontrolled delivery of the coils, misembolization or coil migration treating the aneurysm, either surgically or by endovascular treatment [13,16,17,20]. We believe that hypertenin normal renal artery branches and resulting renal infarcts.…”
Section: Resultsmentioning
confidence: 99%
“…balloons, steel coils and particulate agents has been used in both extra-and intrarenal aneurysms [13,20,22,24]. In three patients with recurrent infarctions, the signs and symptoms of renal embolism disappeared immediHowever, most of these studies have shown that the embolization resulted in occlusion of a renal artery ately after embolotherapy and two patients with haematuria improved immediately after embolotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Some advocate elective repair of large aneurysms, aneurysms in pregnancy [22,23] and aneurysms complicated by arterio-venous fistula formation [30]. Aneurysmectomy is the standard treatment; however, newer treatment options include coil embolization and covered stent grafts [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%